PRIORITY OF THE IDEA OF RELIGIOUS TOLERANCE IN THE POLICY OF THE NEW UZBEKISTAN - Karimov Abdumannof Abdujabborovich (Web of Journals Publishing, 2025)
The article reveals the policy of religious tolerance in New Uzbekistan, its priority areas, the content of the reforms carried out in this area, and their legal basis.
Keywords: New Uzbekistan, religious tolerance, tolerance, domestic and foreign policy, reforms, enlightenment, interethnic harmony.